Little Red Riding Hood - Filipina;Monika (Thaxted Miles Kelly Publishing Ltd, 2015)
the story follows the classic fairy tale of a young girl who sets out to visit her grandmother. Wearing her distinctive red cloak, Little Red Riding Hood travels through the forest, but she encounters a cunning wolf along the way. The wolf tricks her by taking a shortcut to her grandmother's house. When Little Red Riding Hood arrives, she finds that the wolf has disguised himself as her grandmother.